Bhutan Economic Update, December 2016 - World Bank (World Bank, Washington, DC, 2017)
Bhutan maintained solid macroeconomic performance in 2016. Large ongoing investments in hydropower projects, and supportive fiscal and monetary policy have contributed to the momentum in growth. Single-digit inflation, a relatively stable exchange rate, and accumulating international reserves attest to a stable macroeconomic environment. Rapid growth in a relatively calm macroeconomic context is likely to continue for the next few years, which should result in a steady reduction of poverty. Nevertheless, Bhutan’s structural challenges remain: large current account deficits, high public debt, an underdeveloped private sector, and a high youth unemployment rate. To address these challenges, the Royal Government of Bhutan is in the process of revising the Economic Development Policy (EDP) commencing in 2016 and has started preparatory work on the 12th Five-Year Plan (FYP), which will commence in 2018.